Molecular interplay between hyperactive mammalian target of rapamycin signaling and Alzheimer's disease neuropathology in the NS-Pten knockout mouse model. Issue 13 (5th September 2018) - Hodges, Samantha L.; Reynolds, Conner D.; Smith, Gregory D.; Jefferson, Taylor S.; Nolan, Suzanne O.; Lugo, Joaquin N.
Abstract : Dysregulation of the PI3K/Akt/mTOR signaling cascade has been associated with the pathology of neurodegenerative disorders, specifically Alzheimer's disease (AD). Both in-vivo models and post-mortem brain samples of individuals with AD have commonly shown hyperactivation of the pathway. In the present study, we examine how neuron subset-specific deletion of Pten (NS- Pten ) in mice, which presents with hyperactive mammalian target of rapamycin (mTOR) activity, affects the hippocampal protein levels of key neuropathological hallmarks of AD. We found NS- Pten knockout (KO) mice to have elevated levels of amyloid-β, α-synuclein, neurofilament-L, and pGSK3α in the hippocampal synaptosome compared with NS- Pten wild type mice. In contrast, there was a decreased expression of amyloid precursor protein, tau, GSK3α, and GSK3β in NS- Pten KO hippocampi. Overall, there were significant alterations in levels of proteins associated with AD pathology in NS- Pten KO mice. This study provides novel insight into how altered mTOR signaling is linked to AD pathology, without the use of an in-vivo AD model that already displays neuropathological hallmarks of the disease. Abstract : Supplemental Digital Content is available in the text.